2020
DOI: 10.1021/acs.inorgchem.0c01185
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Metal–Organic Frameworks Incorporating Redox-Active Tetrathiafulvalene Ligand: Structures and Effect of LLCT within the MOF on Photoelectrochemical Properties

Abstract: Understanding the effect of charge transfer on the physical properties of metal–organic frameworks (MOFs) is essential for designing multifunctional MOF materials. In this work, three redox-active tetrathiafulvalene (TTF)-based MOFs, formulated as [Co6L6(bpe)6(EtOH)2(MeOH)2(H2O)] n ·5nH2O (1), [Co5(μ3–OH)2L4(bpe)2] n (2), and [CoL­(bpa)­(H2O)] n ·2nH2O (3) (L = dimethylthio-tetrathiafulvalene-bicarboxylate, bpe = 1,2-bis­(4-pyridyl)­ethene, bpa = 1,2-bis­(4-pyridyl)­ethane), are crystallographically character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…34 One of the most extensively used redox-active metal ions in 2D networks is the Fe II /Fe III couple, 25 since the report of mixed-valence Prussian blue, [Fe III 4 {Fe II (CN) 6 } 3 ]· x H 2 O, 35 which has been commonly used as a dye. The commonly used redox-active linkers in CPs and MOFs are the derivatives of tetrathiafulvalene, 36 viologen, 37 quinone, 38 triphenylamine, 39 porphyrin, 40 ferrocene, 41 pyrazine, 42 hexaaminobenzene 43 and tetrazine 44,45 (Chart 1). Among these ligands, quinone and its derivatives have been widely studied for their impressive redox properties.…”
Section: Introductionmentioning
confidence: 99%
“…34 One of the most extensively used redox-active metal ions in 2D networks is the Fe II /Fe III couple, 25 since the report of mixed-valence Prussian blue, [Fe III 4 {Fe II (CN) 6 } 3 ]· x H 2 O, 35 which has been commonly used as a dye. The commonly used redox-active linkers in CPs and MOFs are the derivatives of tetrathiafulvalene, 36 viologen, 37 quinone, 38 triphenylamine, 39 porphyrin, 40 ferrocene, 41 pyrazine, 42 hexaaminobenzene 43 and tetrazine 44,45 (Chart 1). Among these ligands, quinone and its derivatives have been widely studied for their impressive redox properties.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrathiafulvalene (TTF), a sulfur-rich conjugated molecule, has been extensively used as an important electron donor to construct novel charge transfer (CT) multifunctional materials. Naphthalene diimide (NDI), which is electron-deficient, is used as an electron acceptor in various fields. Both of them have reversible multistep redox activity. In 2021, we reported one two-dimensional (2D) MOF, Co-MOF , constructed from organic ligands TTF and NDI, which showed good near-infrared photothermal conversion performance.…”
Section: Introductionmentioning
confidence: 99%
“…In various organic building blocks, the electron-rich tetrathiafulvalene (TTF) unit, owing to its two stable oxidized states, has become a famous redox-active building block in the construction of functional MOFs [1,10]. Among the TTF-carboxylate ligands, dimethylthio-tetrathiafulvalene-bicarboxylate (H 2 TTFBC), tetrathiafulvalene-tetracarboxylate (H 4 TTFTC), and tetrathiafulvalene-tetrabenzoate (H 4 TTFTB) are well-researched in the previous works [10][11][12][13][14][15][16][17]. For H 4 TTFTB, Dincă et al first reported its synthesis and assembly of Zn 2+ in a semiconductive MOF [18].…”
Section: Introductionmentioning
confidence: 99%